Class, gender, sexuality and leadership in Bodija Market, Ibadan, Nigeria. (2019)
Bodija market is the largest informal foodstuff market in Ibadan, southwestern Nigeria. At its inception in the 1980s, leadership of the market space followed long-standing Yoruba tradition, prioritizing the role of older women. This pattern of leadership continued until the mid-1990s, when former government workers, laid off upon implementation of the Structural Adjustment Programme (SAP), moved into the market as traders and eventually as the leaders and market “technocrats.” As a consequence of this, the market women who had held informally recognized leadership positions were sidelined. This development also redefined class within the market structure. The new leaders have impacted the market administration by incorporating symbols of elitism in their leadership style.